Governance Performance Assessment of the Provincial Legislative Council: A Study in South Sulawesi, Indonesia - Ansar, Ansar; Farida, Umi; Rahmatia, Meity; Kurniawaty , Kurniawaty (Jurnal Economic Resource, 2025)
This research analyzes the performance of the South Sulawesi Regional People's Representative Council (DPRD) in carrying out its legislative, supervisory, and budgeting functions. Using a qualitative approach with triangulation, data were collected from March to June 2025 through interviews, observations, and documentation involving 20 informants. The results show improvements in legislative governance with a stronger focus on regulatory implementation and public participation. Supervision is more structured through clear indicators, regular monitoring, and follow-up actions, although data literacy and political dynamics remain challenges. Budgeting provides the highest added value in early planning and monitoring stages to ensure alignment with public needs and fiscal capacity. Overall, the DPRD's performance has become more outcome-oriented; However, professionalism, transparency and integrity still need strengthening. This study contributes a conceptual model linking institutional legitimacy, public accountability, and outcome-based performance for local legislative bodies